Implementasi Pelayanan Pendidikan Bagi Anak Autis Di SLB C Santa Lusia Pematang Siantar (International Forum of Researchers and Lecturers, 2023)
Education is a human right that everyone must have, without exception for children with special needs, especially children with autism. Usually the education that autistic children get is only in special schools (SLB), and the costs incurred for this education are not small but are much more expensive than the regular school system. The effect is that many autistic children cannot experience the world of education because of their parents' economic factors. This research summarizes several problems, namely